ANALISIS SOP (STANDARD OPERATING PROSEDURE) DALAM PRODUKSI ROTI GEMBOPADA USAHA ROTI GEMBONG BITE DI SAMARINDA - Nur Syahdi (Jurnal Administrasi Bisnis Fisipol Unmul, 2020)
The results showed that the SOP used was the SOP in the simplest form which only had a few activities and decision making. In the production process there are five stages carried out during the production process, namely, preparing raw materials, stirring the dough into a mixer, the process of rolling bread, the process of developing bread and the process of developing the dough ready to bake. Here the raw materials in the form of main raw materials namely wheat flour, capital in the form of owner's personal capital, machines in the form of tools used during the production process and work force are very influential during the production process because workforce is the main actor in the production of bread king. As one of the kingpin bread businesses in Samarinda, it is expected that the staff of the kingpin bread must continue to improve and maintain the quality of the production produced, that is bread kingpin and still maintain the quality of human resources namely labor. The most important thing must not be forgotten is that labor is a very very important factor of production in every production process that should be a benchmark to find out whether the system implemented has been implemented properly.